Existence Results for a Class of Semilinear Fractional Partial Differential Equations with Delay in Banach Spaces - Bo Zhu; Baoyan Han; Xiangyun Lin (Journal of Function Spaces)
In this paper, we consider a class of nonlinear time fractional partial differential equations with delay. We obtain the existence and uniqueness of the mild solutions for the problem by the theory of solution operator and the general Banach contraction mapping principle. We need not extra conditions to ensure the contraction constant 0<k<1. Therefore, under some general conditions, we obtain our main results.